THE ROLE OF BRAND TRUST AS A MEDIATOR BETWEEN PRODUCT QUALITY AND INNOVATION ON PURCHASE INTENTION OF KIMPLAST DISTRIBUTORS - Jeremy Lauren Mahendra; Thomas Srefanus Kaihatu (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study examines the effect of Product Quality and Product Innovation on the Purchase Intention of KIMPLAST distributors, with Brand Trust serving as a mediator. A quantitative approach was employed via a survey of 109 active KIMPLAST distributors across Eastern Indonesia. Data were collected using a structured 5-point Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess direct, indirect, and mediating relationships. The results indicate that Product Quality and Product Innovation have a positive and significant effect on Brand Trust, which subsequently enhances distributors’ Purchase Intention. Brand Trust is confirmed as a vital mediator that strengthens the influence of product attributes on purchasing decisions in a B2B context. This study contributes to B2B literature by providing empirical evidence on the crucial mediating role of Brand Trust within the industrial plastic products distribution sector. Consequently, companies should prioritize strategies that enhance Brand Trust through product quality and innovation to boost distributor loyalty and stabilize purchasing behavior. The study is limited by its cross-sectional design and a sample size of 109 distributors, suggesting future research should expand the sample size and explore additional variables such as price or after-sales services.